The new geo-governance : a baroque approach - Paquet, Gilles (Governance series (Ottawa, Ont.), 2005)
"Over the last few decades, the Westphalian nation-state has lost its hegemonic position in the system of geo-governance. A dispersive revolution has led to the emergence of powerful newly networked business organizations, new subsidiarity-focused governments, and increasingly virtual, elective, and malleable communities. This in turn has led to the crystallization of distributed governance regimes, based on a wider variety of more fluid and always evolving groups of stakeholders. In The New Geo-Governance, Gilles Paquet develops a general conceptual framework to deal with the new evolving reality of global governance. He uses this framework to critically examine the evolving territorial governance (hemispheric governance, meso-innovation systems, smart city-regions) and tackles the more complex governance challenges raised by sustainability and common-property resources like oceans. Paquet further explores the implications of this emerging baroque polycentric geo-governance on the new forms of stewardship and its impact on citizenship, federalism, and other technologies of coordination, and reflects on the sort of subversive bricolage required if the missing mechanisms for effective coordination are to be put in place. The New Geo-Governance will be of great interest to students and scholars interested in governance, organizational design, international affairs, and political studies."--Jacket